An in situ spectroscopic study of the ruthenium catalyzed carbonylation of piperidine starting with triruthenium dodecacarbonyl. The importance of path dependence in homogeneous catalysis - Liu, G. (2014)
10.1016/S1381-1169(00)00517-3